IMPLEMENTATION OF THE INDONESIAN NAVY'S STRATEGY IN THE APPLICATION OF UNDERWATER ACOUSTIC TECHNOLOGY IN THE SUNDA STRAIT TO SAFEGUARD NATIONAL SOVEREIGNTY AT SEA: IMPLEMENTASI STRATEGI TENTARA NASIONAL INDONESIA ANGKATAN LAUT DALAM PENERAPAN TEKNOLOGI AKUSTIK BAWAH AIR DI WILAYAH SELAT SUNDA DALAM RANGKA MENJAGA KEDAULATAN NEGARA DI LAUT - Jazim Aziz M; Moh. Ikhwan Syataria; Andi Sultan Alimudin (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This study explores the application of underwater acoustic technology by the Indonesian Navy (TNI AL) to enhance security in the Sunda Strait, as part of Indonesia's commitment to becoming a World Maritime Axis (PMD). With increasing threats from foreign submarines and unmanned vehicles, this research employs a qualitative descriptive approach through in-depth interviews, direct observations, and document analysis to identify the challenges and opportunities faced by TNI AL. The results indicate that although TNI AL has adopted advanced detection technologies, such as sonar and sentinel systems, resource and infrastructure constraints remain significant obstacles. Therefore, it is recommended that TNI AL adopt an integrated approach involving adequate resource allocation, inter-agency harmonization, and strengthening of deterrence strategies. By integrating aspects of diplomacy, military, economy, and information, it is hoped that the defense and security of the Sunda Strait can be effectively enhanced, safeguarding Indonesia's maritime sovereignty amid complex security dynamics.